Association Between Body Mass Index and Handgrip Strength in Manual Handling Workers - Rindha Puji Rahayuningrum; Fajar Syamsudin (Jurnal Impresi Indonesia, 2026)
Nutritional status significantly influences workers’ physical capacity, particularly muscle strength required for manual handling activities. This study aimed to evaluate the distribution of body mass index (BMI) and handgrip strength and to determine their association among manual handling workers at CV. Laksana Es Kristal. This cross-sectional correlational study involved 20 respondents selected through purposive sampling. Body mass index was assessed using height and weight measurements, while handgrip strength was measured using a handgrip dynamometer. Data were analyzed using the Spearman correlation test. The findings showed that the mean BMI was 20.22 kg/m², with 70% of respondents classified as having a normal BMI category. The mean handgrip strength was 40.12 kg, with most respondents categorized as having moderate strength. Statistical analysis revealed a significant positive association between BMI and handgrip strength (p = 0.041; r = 0.46), indicating a moderate correlation. Workers with optimal nutritional status demonstrated greater muscle strength. These findings suggest that BMI contributes to variations in physical work capacity, although muscle strength is also influenced by other physiological and occupational factors. This study highlights the importance of integrating nutritional monitoring and physical fitness management into occupational health programs to support workers’ functional performance and reduce musculoskeletal risks.